REGULATION REFORM AND IMPLEMENTATION OF SANCTIONS FOR DRUG ABUSERS IN INDONESIA BASED ON LEGAL CERTAINTY - Yulia Syafitri; Eriyantouw Wahid; Heru Susetyo (PT. Radja Intercontinental Publishing, 2026)
This study examines the urgency of regulatory reform and reform of the sanction system for drug abusers in Indonesia based on the principle of legal certainty. The main issues cover three dimensions: first, normative problems in the implementation of Law Number 35 of 2009 concerning Narcotics; second, a comparison of the sanction application models between Indonesia, Portugal, and the Netherlands; and third, the ideal concept of narcotics regulatory reform that can guarantee legal certainty, benefit, and justice. This study uses a normative juridical method with four approaches: statute approach, historical, comparative, and case study. The results of the study indicate that Law No. 35 of 2009 contains several structural weaknesses, including the ambiguity of the definition of abuser, addict, and victim; the potential for multiple interpretations in the article on narcotics possession; the dominance of a criminalization approach that has the potential to criminalize users; and the absence of specific provisions for sanctions for children. Comparatively, Portugal and the Netherlands have implemented a health-based paradigm and harm reduction as alternatives that have proven to be more effective. The ideal concept of national narcotics law reform must reflect the three objectives of law according to Gustav Radbruch, namely certainty (Rechtssicherheit), benefit (Zweckmassigkeit), and justice (Gerechtigkeit).